Pemodelan Relay Diferensial Pada Transformator Daya 25 MVA Menggunakan Anfis - Firdaus, Hari; Zakri, Azriyenni Azhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Power transformer is an electrical device that is utilized to convert the electrical power from different voltage level. The fault occurs in the power transformer will inhibit the process of distributing electrical power to the consumer. Therefore, the protection system on power transformers is essential in power systems reliability. Power system can be reliable, if the protective devices work well when there is fault. Under fault conditions, protective devices have an important role in detecting any fault and separating the faulted parts of the system. This research will be conducted on 25 MVA of power transformer at gas power plant (case study: PT Riau Power). Matlab / Simulink was use for modelling differential relay. The simulation of short circuit have been created at three different locations, namely : internal, external 1, and external 2, respectively. The result of short circuit simulation using differential relay to input data used for the application of ANFIS method. Furthermore, these data were classified into three different input for ANFIS such as : internal with eksternal 1, internal with external 2, and internal, external 1 with external 2, respectively. The error result of ANFIS training for type of internal and external fault 1 is 0,00000086148, for types of internal and external fault 2 by 0,00000092462 and internal, external 1 and external 2 of 0,0000019162. The training results have obtained the smallest error value is the type fault of internal and external 1.Keywords : ANFIS, differential relay, power transformer, resetting